Targeting membrane androgen receptors in tumors. (August 2013) - Lang, Florian; Alevizopoulos, Konstantinos; Stournaras, Christos
Abstract : Introduction: In the last decade androgen actions that are originated from non-genomic, rapid signaling have been described in a large number of cell models and tissues. These effects are initiated through the stimulation of membrane androgen-binding sites or receptors (mAR). Although the molecular identity of mARs remains elusive, their activation is known to trigger multiple non-genomic signaling cascades and to regulate numerous cell responses. In recent years specific interest is being paid to the role of mARs in tumors. Specifically, it was demonstrated that mAR activation by non-permeable testosterone conjugates induced potent anti-tumorigenic responses in prostate, breast, colon and glial tumors. In addition, in vivo animal studies further emphasized the potential clinical importance of these receptors. Areas covered: This review will summarize the current knowledge on the mAR-induced non-genomic, rapid androgen actions. It will focus on the molecular signaling pathways governed by mAR activation, discuss latest attempts to elucidate the molecular identity of mAR, address the plethora of cell responses initiated by mAR and evaluate the potential role of mAR and mAR-specific signaling as possible therapeutic targets in tumors. Expert opinion: mAR and mAR-induced specific signaling may represent novel therapeutic targets in tumors through the development of specific testosterone analogs.